2019
DOI: 10.2118/195504-pa
|View full text |Cite
|
Sign up to set email alerts
|

Alkali/Cosolvent/Polymer Flooding of High-TAN Oil: Using Phase Experiments, Micromodels, and Corefloods for Injection-Agent Selection

Abstract: Summary Chemical enhanced oil recovery (EOR) leads to substantial incremental costs over waterflooding of oil reservoirs. Reservoirs containing oil with a high total acid number (TAN) could be produced by the injection of alkali. Alkali might lead to the generation of soaps and emulsify the oil. However, the generated emulsions are not always stable. Phase experiments are used to determine the initial amount of emulsions generated and their stability if measured over time. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 64 publications
1
40
0
Order By: Relevance
“…The commercial price of Na 2 SO 4 is USD 80–120/Ton. The average price of this salt is around 0.1 USD/kg, which is much lower than the average price of polymer, alkaline, and co-solvent (3 USD/kg, 0.25 USD/kg, and 3 USD/kg, respectively [ 42 ]). The spiked amount of sulfate to design sulfate-modified water for this study is 8–16 g/L (two times and four times the sulfates in SSW).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The commercial price of Na 2 SO 4 is USD 80–120/Ton. The average price of this salt is around 0.1 USD/kg, which is much lower than the average price of polymer, alkaline, and co-solvent (3 USD/kg, 0.25 USD/kg, and 3 USD/kg, respectively [ 42 ]). The spiked amount of sulfate to design sulfate-modified water for this study is 8–16 g/L (two times and four times the sulfates in SSW).…”
Section: Resultsmentioning
confidence: 99%
“…The micromodel is an artificial structure micromodel or homogeneous micromodel, due to its random distribution of circular grains. Such micromodels have been previously used for several EOR investigations [ 39 , 40 , 41 , 42 ]. Figure 2 shows pore structure images and dimensional measurements of the model, and Table 2 provides porosity and permeability values.…”
Section: Materials and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the micromodel is placed under a microscope equipped with a high-speed camera (qualitative evaluation). There is a broad range of micromodel types that can be used for flooding experiments such as GSG micromodels based on Bentheimer CT images [ 15 , 88 , 89 ], completely transparent real porous-media-resembling plastic micromodels (Hogeweg et al 2018) and symmetric micromodels as presented in the work of Galindo-Rosales [ 61 ] and Scholz et al [ 59 ]. An overview image of a GSG micromodel as used by Wegner et al [ 15 ], Rock et al [ 30 ], Gaol et al [ 89 , 90 ] and Hincapie et al [ 29 ] as an example is shown by Figure 13 .…”
Section: Viscoelasticity In Enhanced Oil Recoverymentioning
confidence: 99%
“…Alkaline injection has also been coupled with other enhanced oil recovery methods including surfactant injection [20], polymer injection [21,22], polymer and surfactant flooding [23][24][25][26], smart water injection [27], and even steam-assisted gravity drainage [28]. Potts and Kuehne [29] underwent experiments using fired Berea sandstone cores and reservoir cores to compare the difference between both when undergoing polymer/alkaline injection.…”
Section: Introductionmentioning
confidence: 99%